2002
DOI: 10.1002/pat.230
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance bismaleimide matrices: cure kinetics and mechanism

Abstract: Kinetics and mechanism of equifunctional 4,4′‐(N,N′‐bismaleimide)‐diphenylmethane/2,2′‐diallyl‐bisphenol A (BMDM/DABPA) and model (phenylmaleimide/2,2′‐diallylphenol) (PMI/AP) systems have been studied in the temperature range 140–400 °C using IR‐, 1H‐ and ­13C‐NMR spectroscopy, gas chromatography–mass spectrometry GCMS), differential scanning calorimetry (DSC) and isothermal calorimetry. It was established that the cure mechanism consists a unique combination of step‐wise and chain polymerization and polycond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 19 publications
3
84
0
Order By: Relevance
“…This may indicate that polymerization mechanism is different because it is known that purple or red color is obtained upon anionic polymerization of BMI that usually leads to a lower molecular weight polymer [23]. Absence of red or purple color in the case of isopropanol indicates that BMI probably underwent a free radical polymerization as reported elsewhere [24]. The chemical structures of modified BMI-PEI as well as modified BMI-PSF were analyzed by ATR-FTIR and XPS spectroscopy as found elsewhere [25,26].…”
Section: Resultsmentioning
confidence: 82%
“…This may indicate that polymerization mechanism is different because it is known that purple or red color is obtained upon anionic polymerization of BMI that usually leads to a lower molecular weight polymer [23]. Absence of red or purple color in the case of isopropanol indicates that BMI probably underwent a free radical polymerization as reported elsewhere [24]. The chemical structures of modified BMI-PEI as well as modified BMI-PSF were analyzed by ATR-FTIR and XPS spectroscopy as found elsewhere [25,26].…”
Section: Resultsmentioning
confidence: 82%
“…This difference in reactivity for 2-allylphenol/PMI and DABA/PMI was attributed to steric repulsion of DABA. Subsequently, Morgan et al 13,14 reported that the curing mechanism of DABA/BMIM consisted of the ene addition reaction of the ally group to maleimide one, subsequent chain polymerization of maleimide and propenyl groups generated by the ene reaction and etherification by the dehydration reaction of the phenol moieties, based on the FTIR analysis of the reaction of DABA and BMI ( Figure 6). The experimental result from remote fiber optic near-infrared spectroscopy by Mijoviae and Andjeliae 28 also supported the occurrence of the etherification reaction, but a chemical structure was not proposed.…”
Section: Resultsmentioning
confidence: 99%
“…12 Fourier Transform Infrared (FTIR) analysis of DABA has shown that a stepwise ene reaction and subsequent chain polymerization in addition to an etherification reaction occurs in the production of DABA/BMIM. 13,14 Although the fully cured DABA/BMIM possesses superior thermal stability and mechanical properties, its typical curing condition (230-250 1C/4-6 h) are too severe to allow it to be applied to a wide range of uses such as general purpose electronics and structural materials. We had already reported that the BMIM cured with tung oil or dehydrated castor oil at 200 1C for 2 h has a relatively high glass transition temperature (T g ) with high tensile strength and modulus, 15,16 and that the Diels-Alder polymerization product of furfuryl ester-terminated butylene succinate oligomer and BMIM has flexural strength properties superior to poly(butylene succinate).…”
Section: Introductionmentioning
confidence: 99%
“…However, the composites have different curing mechanism from DBA/BDM resin. For DBA/BDM resin, its curing mechanism contains multiple reactions, for example 'Ene' and 'Diels-Alder' reactions between maleimide group of BDM and allyl group of DBA, and the self-polymerization of BDM via C=C bonds (Figure 5a) [20,21]; while in the case of MPSA/DBA/BDM system, besides above reactions of DBA/BDM, there is a Michael reaction between maleimide and -NH 2 groups [22]. This additional reaction not only supplies a chemical bonding between MPSA and DBA/BDM (Figure 5b) to guarantee a good dispersion of MPSA in the matrix, but also leads to a different structure of crosslinked network.…”
Section: Measurementsmentioning
confidence: 99%